Association of anticoagulation dose and survival in hospitalized COVID‐19 patients: A retrospective propensity score‐weighted analysis. (4th November 2020) - Ionescu, Filip; Jaiyesimi, Ishmael; Petrescu, Ioana; Lawler, Patrick R; Castillo, Edward; Munoz‐Maldonado, Yolanda; Imam, Zaid; Narasimhan, Mangala; Abbas, Amr E.; Konde, Anish; Nair, Girish B.
Abstract: Background: Hypercoagulability may contribute to COVID‐19 pathogenicity. The role of anticoagulation (AC) at therapeutic (tAC) or prophylactic doses (pAC) is unclear. Objectives: We evaluated the impact on survival of different AC doses in COVID‐19 patients. Methods: Retrospective, multi‐center cohort study of consecutive COVID‐19 patients hospitalized between March 13 and May 5, 2020. Results: A total of 3480 patients were included (mean age, 64.5 years [17.0]; 51.5% female; 52.1% black and 40.6% white). 18.5% (n = 642) required intensive care unit (ICU) stay. 60.9% received pAC (n = 2121), 28.7% received ≥3 days of tAC (n = 998), and 10.4% (n = 361) received no AC. Propensity score (PS) weighted Kaplan‐Meier plot demonstrated different 25‐day survival probability in the tAC and pAC groups (57.5% vs 50.7%). In a PS–weighted multivariate proportional hazards model, AC was associated with reduced risk of death at prophylactic (hazard ratio [HR] 0.35 [95% confidence interval CI 0.22‐0.54]) and therapeutic doses (HR 0.14 [95% CI 0.05‐0.23]) compared to no AC. Major bleeding occurred more frequently in tAC patients (81 [8.1%]) compared to no AC (20 [5.5%]) or pAC (46 [2.2%]) subjects. Conclusions: Higher doses of AC were associated with lower mortality in hospitalized COVID‐19 patients. Prospective evaluation of efficacy and risk of AC in COVID‐19 is warranted.